Pharmacokinetics of Ampreloxetine, a Norepinephrine Reuptake Inhibitor, in Healthy Subjects and Adults with Attention-Deficit/Hyperactive Disorder or Fibromyalgia Pain - Kanodia, Jitendra; Lo, Arthur; Baldwin, R. Michael; Graham, Richard A.; Bourdet, David L. (Clinical pharmacokinetics, 2021)
Background and Objective Ampreloxetine is a novel norepinephrine reuptake inhibitor in development for the treatment of symptomatic neurogenic orthostatic hypotension. The objectives of this analysis were to define the pharmacokinetics of once-daily oral ampreloxetine and provide dose recommendations for clinical development. Methods We fitted a population pharmacokinetic model to ampreloxetine plasma concentrations from single- and multiple-ascending dose trials in healthy subjects and two phase II studies in adult subjects with attention-deficit/hyperactive disorder or fibromyalgia at doses of 2–50 mg. Results Ampreloxetine pharmacokinetics was best described by a two-compartment model with first-order absorption and elimination. The terminal half-life was 30–40 h, resulting in sustained drug concentrations for the entire 24-h dosing interval at steady state. Covariates of age, weight, or renal impairment did not impact ampreloxetine exposure. Cytochrome P450 2D6 phenotype had no influence on ampreloxetine exposure. Sex and smoking status were identified as statistically significant covariates, suggesting a role for cytochrome P450 1A2 in the elimination of ampreloxetine. Despite statistical significance, differences in ampreloxetine exposure in male vs female subjects and smokers vs non-smokers were not clinically meaningful at the recommended dose. At the 10-mg dose, > 75% norepinephrine transporter inhibition and < 50% serotonin transporter inhibition are anticipated for adult subjects. Conclusions The population pharmacokinetic model effectively described the plasma concentration–time profile of ampreloxetine after single and multiple doses. Population pharmacokinetic/pharmacodynamic analysis justified using a fixed dosing regimen with no dose adjustments across a broad population and can be used to inform dosing strategies in future clinical studies. Clinical Trial Registration ClinicalTrials.gov identifier numbers NCT01693692 (fibromyalgia); NCT01458340 (attention-deficit/hyperactive disorder).